2005
DOI: 10.1073/pnas.0506810102
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways control recruitment and maintenance of myosin II at the cleavage furrow during cytokinesis

Abstract: The correct localization of myosin II to the equatorial cortex is crucial for proper cell division. Here, we examine a collection of genes that cause defects in cytokinesis and reveal with live cell imaging two distinct phases of myosin II localization. Three genes in the rho1 signaling pathway, pebble (a Rho guanidine nucleotide exchange factor), rho1, and rho kinase, are required for the initial recruitment of myosin II to the equatorial cortex. This initial localization mechanism does not require F-actin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 47 publications
11
101
3
1
Order By: Relevance
“…Myosin II is also known to accumulate at the cleavage furrow and thereby drive cytokinesis. [27][28][29] Immunohistochemical staining also revealed the co-localization of GC UNC-45 with myosin II at the cleavage furrow in mitotic ovarian cancer cells during both metaphase and anaphase ( Figure 5, C and D), consistent with the role of GC UNC-45 as a chaperone that facilitates the correct assembly of myosin II during cytokinesis.…”
Section: Co-localization Of Gc Unc-45 With Myosin II and The Effect Osupporting
confidence: 49%
“…Myosin II is also known to accumulate at the cleavage furrow and thereby drive cytokinesis. [27][28][29] Immunohistochemical staining also revealed the co-localization of GC UNC-45 with myosin II at the cleavage furrow in mitotic ovarian cancer cells during both metaphase and anaphase ( Figure 5, C and D), consistent with the role of GC UNC-45 as a chaperone that facilitates the correct assembly of myosin II during cytokinesis.…”
Section: Co-localization Of Gc Unc-45 With Myosin II and The Effect Osupporting
confidence: 49%
“…ZEN-4 is the only kinesin-6 family protein found in Caenorhabditis elegans, and there are two kinesin-6 family proteins found in Drosophila, Pavarotti and KLP67A (Kollmar and Glockner, 2003). Whereas loss of Pavarotti led to a complete failure of cleavage furrow ingression, loss of Zen-4 led to a late cytokinesis defect where the cleavage furrow would initiate but eventually regressed (Adams et al, 1998;Raich et al, 1998;Dean et al, 2005). We have shown that Kif12 null cells have similar cytokinesis defects; some cells fail to initiate cleavage furrow formation (Lakshmikanth et al, 2004), whereas others initiate but fail to complete cytokinesis.…”
Section: Kif12 Is Required For the Localization Of Ddincenp At The CLmentioning
confidence: 60%
“…The contribution of the motor domain of myosin-II proteins to their localization to the cleavage furrow or the contractile ring had previously been unclear because the accumulation of myosin-II to the cleavage furrow or contractile ring was typically concurrent with its filamentogenesis and depended heavily on the tail moiety, but not on the motor domain (Dean et al, 2005). Some scaffold proteins might tether the rod of myosin-II filaments to the equatorial cortex in these cells.…”
Section: Discussion the Motor Properties Of Myo3 Are Relevant To Its mentioning
confidence: 99%